PENGEMBANGAN PELUANG KEWIRAUSAHAAN JASA KEPARIWISATAAN SEJARAH DAN BUDAYA INDONESIA MELALUI PROGRAM MAGANG KEWIRAUSAHAAN - Rokhnuin, M. Nur (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2003)
The objectives  of  this  program  :  (l)To     provide  the  knowledge,  skill  and experience in the tourism business, theoritically and practically; (2) To provide knC}'."fl~ggesk, ill  and  practice  to  the  studens  about  the  Indonesian  Culture  Historry Tourism; (3) To push ahead and to motive the students to be a new businessmen m the field of tourism; (4) To create the partnership between University with the middle and small business, especially business in the field of.the tourism, (5) To push the acceleation of the Indonesian Economic Recovery through developing the new businessmen, and (6) This program is expected to  be embryo for the' birth of study pro~ram of tourisn  in Yogyakarta State University. As for target of the aoutput of the activity of apprentice to business in filed of tourism as the following: (1) Minimally %0 % from the participants of appretice will be ready to be a new businessmen in thefield tourism service, especially management and torism amnagning, touris guide, journey tourism guide, avalilabillity for Inodnonesian history arid culture tourism package; (2) Minimally 50 % from the partisipants  of apprentice will be ready to prudoce the proposal of e new businessmen in the filed tourism, especially manageme~t for. tourism managening, t<?ursmguide, journey tounsm  guide, availability of   Indonesian histony  and culutre tounsm  packade. (#) To create partnership between University with small and midle business, especially business in the filed of tourism; (4).  Apprentice participants and guidance lekturer can increase their knowledge and skill, especially work skill and practical knowledge. While the side of partner can increase management and marketing.The pattern of apprentice program realization is brougtht aout the following : selecting the participants, providing, transferring the knowledge skill and experience from tourism industry service to the  apprentice and apprentice participant  students making proposal for building a new business in the field of tourism, both for domestic tourst service and a foreign tourist  service. This new business can be pioneered in business service.  For the first stage they can cooperate with the side of the pertnerts who are in Yogyakarta or the other,place ..'            The apprentice program realization which as gone on for ane month, is followed11 students.   There' isno significant obstacle for the apprentice realization in the field. From the 11 apprentice participants, there are 4 student who have the best achievement and then have being taken as a freelance personnel by the partner side.  For next plan the team of apprentice is expected to be able to open the tour and travel bussines in thecampus, and as the  first  step,  it  is included in INWUB program  which has  been in presence.Key words    :  apprentice, and enterpreneurship